Relative Sea Level Changes and Worsening Floods in the Western Pampanga Delta: Causes and Some Possible Mitigation Measures - Siringan, Fernando; Rodolfo, Kelvin (Science Diliman: A Journal of Pure and Applied Sciences, 2012)
Despite declining rainfall, flooding continues to worsen around the northern end of Manila Bay. In Pampanga, flooding is enhanced by siltation of streams by sediments from the 1991 Mt. Pinatubo eruption, but the entire region has always been flood-prone, and Bulacan and Metro Manila, far from Pinatubo, also suffer worsening floods. Urbanization and deforestation are blamed, but have less impact than local sea level rise. Global warming causes the ocean surface to rise only 2 mm/yr; localized subsidence of the region from both natural and anthropogenic causes is an order of magnitude faster. Movements associated with faulting and the Pinatubo and Taal volcanoes probably are less important than the compaction of deltaic sediments under their own accumulating weights. All natural causes of subsidence are dwarfed by the contribution from excessive groundwater withdrawal, which greatly facilitates natural sediment dewatering and compaction. Several centimeters per year of documented subsidence at well sites have been corroborated by recent resurveys of elevation benchmarks established in the 1950s. In the short-term, flooding can be ameliorated by restoring original channel widths and by modifying current aquaculture practices. In the longer term, reforestation should also help by increasing infiltration and decreasing erosion and siltation. Flooding will inexorably continue in the coming century, however, both from natural compaction of delta sediments and from global sea level rise. Subsidence will continue to accelerate if the use of groundwater by the growing population is not regulated and reduced.